Ethnoecological Perspectives on Agroforestry Practices for Climate Change Mitigation and Adaptation - Kamakaula, Yohanes (West Science Interdisciplinary Studies, 2024)
This research investigates the ethnoecological perspective of agroforestry practices for climate change mitigation and adaptation. Through a literature review method, we analyze relevant literature from various sources to uncover the relationship between local wisdom and agroforestry practices in addressing the challenges of climate change. Findings indicate that the ethnoecological perspective plays a crucial role in shaping sustainable and adaptive agroforestry practices by integrating local knowledge of local ecology and climate patterns with modern scientific knowledge. Agroforestry not only contributes to mitigating greenhouse gas emissions and carbon storage but also provides effective adaptation solutions through season-based planting arrangements and the cultivation of species resilient to extreme conditions. By recognizing the value of local wisdom and knowledge and actively involving community participation in agroforestry management, we can strengthen the resilience and sustainability of agroforestry systems in facing climate change.